Assessment of tubule occlusion properties of an experimental stannous fluoride toothpaste: A randomised clinical in situ study. (September 2018) - West, Nicola X.; Seong, Joon; Hellin, Nicola; Macdonald, Emma L.; Jones, Siân B.; Creeth, Jonathan E.
Abstract: Objectives: To evaluate the ability of a modified in situ model to differentiate dentinal tubule occlusion properties of toothpaste formulations over 10 days of treatment. Methods: This was a single-centre, three-treatment period, crossover, randomised, single-blind study with healthy participants wearing two lower oral appliances, each retaining four dentine samples, for 10 treatment days during each period of the study. Samples were power-brushed ex vivo twice on each treatment day with a Test toothpaste containing 0.454% stannous fluoride, a Control fluoride toothpaste containing 0.76% sodium monofluorophosphate, or mineral water. Dentine samples were subjected to in situ acid challenge (orange juice) on Days 9 and 10. Scanning electron microscopy images obtained at baseline and after 1, 4, 8 and 10 days of treatment were graded for degree of surface coverage by four calibrated examiners; the primary study endpoint was Day 8. Results: After 4, but not 8, days' treatment, the degree of tubule occlusion increased in the dentine samples treated with the Test or Control toothpastes compared with the water-treated samples (p < 0.01 and p < 0.05, respectively). Following the acid challenge (Day 10), there was a statistically significantly greater degree of occlusion in the Test toothpaste-treated dentine samples compared with those treated with water (p < 0.01). No other comparisons were statistically significant. All study treatments were generally well-tolerated. Conclusions: This modified in situ model was unable to demonstrate statistically significant between-treatment differences in dentinal tubule occlusion after 8 days. Conversely, there are recognised developments that could be made to better identify product differences. Clinicaltrials.gov: NCT02768194. Clinical significance: Dentine hypersensitivity can be managed through brushing with stannous fluoride toothpastes, which occlude patent dentine tubules. Clinical studies measure pain but in situ models are needed to demonstrate occlusion intra-orally. However, this study did not demonstrate superior occlusion with stannous toothpaste; further methodological development is required to investigate its mode of action.